Internet of vehicles -- technologies and services : third International Conference, IOV 2016, Nadi, Fiji, December 7-10, 2016, Proceedings /: third International Conference, IOV 2016, Nadi, Fiji, December 7-10, 2016, Proceedings. (2016) - Unknown
No abstract available